2012
DOI: 10.1021/cs2006229
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Rhodium Cocatalysts for Photocatalytic Steam Reforming of Methane over Alkaline Titanate

Abstract: Photocatalytic steam reforming of methane (PSRM; 2 H2O (g) + CH4 → 4 H2 + CO2) was examined over metal-loaded K2Ti6O13 photocatalysts. Although the production rate was improved by loading Pt cocatalyst on the K2Ti6O13 photocatalyst, unfavorable formation of CO and gradual deactivation of photocatalyst were observed. On the other hand, a Rh-loaded K2Ti6O13 sample showed two times higher activity than the Pt-loaded one did, and promoted the PSRM selectively without deactivation for many hours. In the highly acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 57 publications
0
68
0
Order By: Relevance
“…The photocatalytic activity increased with decreasing particle size for three systems with average particle sizes in the 2e7 nm range. Shimura et al demonstrated that metallic Rh nanoparticles (typically around 9 nm) were preferred for the hydrogen evolution reaction, whereas larger (typically in the range of 25e50 nm) oxidic Rh particles were preferred as catalysts for the oxidative reaction (CH 4 þ 2H 2 O / CO 2 þ 8H þ ) by using Rh/K 2 Ti 6 O 13 materials prepared by photodeposition [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The photocatalytic activity increased with decreasing particle size for three systems with average particle sizes in the 2e7 nm range. Shimura et al demonstrated that metallic Rh nanoparticles (typically around 9 nm) were preferred for the hydrogen evolution reaction, whereas larger (typically in the range of 25e50 nm) oxidic Rh particles were preferred as catalysts for the oxidative reaction (CH 4 þ 2H 2 O / CO 2 þ 8H þ ) by using Rh/K 2 Ti 6 O 13 materials prepared by photodeposition [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The photogenerated electrons reduce protons at the NP metal surfaces. Shimura et al [49,50] and Maeda et al [37] suggested that electron extraction from the conduction band of ZGON by rhodium oxide is less efficient than that achieved by Rh metal. This suggests that rhodium oxide cocatalyst reduction is necessary for obtaining active photocatalysts.…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable to assume that metal NPs would also be active sites in H2 generation during photocatalytic water splitting. Shimura et al [49,50] have investigated the effects of the oxidation states of Rh NPs supported on Sr2Ti6O13 in the photocatalytic water-splitting reaction, and found that Rh metal catalyzes photocatalytic H2 production better than rhodium oxide does. Our earlier research on Rh particles supported on g-C3N4 also demonstrated that Rh metal particles are preferable for the H2 production reaction [27].…”
Section: H2 Oxidationmentioning
confidence: 99%
“…The mixture of rhodium metal and oxide co-catalysts also enhanced the activity of a Na 2 Ti 6 O 13 photocatalyst. 162 …”
Section: Photocatalytic Steam Reforming Of Methanementioning
confidence: 99%